Analisis Skema Aktansial dan Model Fungsional Greimas pada Cerita Pendek Tsuru no Ongaeshi - Budi Santoso; Diah Soelistyowati (Japanese Research on Linguistics, Literature, and Culture, 2020)
AbstractA short story is one of the literary works that is not very long and generally focuses on a single event with one or two characters. This paper tries to describe the narrative structure in the story ãƒ„ãƒ«ã®æ©è¿”ã—. Source of data uses short story ãƒ„ãƒ«ã®æ©è¿”ã—, taken fromÂ  https://www.wasabi-jpn.com. The research approach uses structuralism especially Greimasâ€™s actantial schemeÂ  and the functional narrative model. The results show that the short story ãƒ„ãƒ«ã®æ©è¿”ã—Â  formed by one functional narrative model and 6Â  actual schemes. The functional narrative model consists of initial situation, transformation stage (qualifying test, main test, glorifying test), and the final situation. From 6 actan schemes, there are 4 complete actantial schemes and 2 incomplete actantial schemes (actantial schemes without opponent). There are 6 acting roles that make up the short story ãƒ„ãƒ«ã®æ©è¿”ã—;sender, receiver, subjects, objects, Â helpers,Â  and opponent .